Strengthening and rehabilitation of RC beam column joints using carbon FRP jacketing and epoxy resin injection. - Karayannis, Chris G. (Earthquake engineering & structural dynamics.)
The scope of this study is to present results of an experimental investigation on the behaviour of critical external beam column joints repaired or/and strengthened with a combination of epoxy resin injections and carbon fibre reinforced plastics (C-FRP) sheets and to extract useful and practical conclusions. The experimental program comprises 12 external beam column joint connection subassemblages tested in cyclic loading. From the observed responses of the examined specimens it can be deduced that the technique of epoxy resin injections is appropriate for the total rehabilitation of the joints seismic capacity, since no damages have been observed at the joint area of the specimens after the repair. The combination of this technique with the use of C-FRP sheets leads to a significant improvement of the loading capacity, the energy absorption and the ductility and finally it leads to improved type of damages compared with the damage modes of the specimens during the initial loading. Shortcomings of the application of C-FRP sheets for practical use are also pointed out.